A Novel Scheduling Service for Distribution Pilot Protection Over a WiMAX Network - H. Khan, Reduan; Mahata, Kaushik; Y. Khan, Jamil (Recent Advances in Communications and Networking Technology, 2013)
One of the key objectives of a smart grid is to provide reliable protection and control mechanisms in distribution networks. Pilot protection schemes being one of the most effective methods of protecting networked distribution lines, are extensively used in high voltage transmission grids. Pilot protection schemes use high-speed, interrelay communications for fast fault detection and isolation. The use of a broadband wireless access network such as IEEE802.16 based WiMAX can significantly extend the reach of a pilot protection scheme by providing a fast, reliable and pervasive communications alternative. However, significant challenges exist in terms of radio resource allocation to support such an event-driven, machine-to-machine (M2M) communication traffic over a WiMAX network which is traditionally optimized for various multimedia applications. As a solution, this paper proposes a novel radio resource scheduling service called Expedited Effort (EE) that uses a differentiated random access and a prioritized grant mechanism to transfer the time-critical pilot protection messages. Performance evaluation is conducted for both of the existing Best Effort (BE) and the proposed EE services under varying traffic load and channel conditions using a discrete-event simulation model based on OPNET. The simulation study reveals that while the existing BE service fails to meet the challenging QoS requirements of a pilot protection scheme, the proposed EE service provides satisfactory performance even under quite difficult channel conditions.
Keywords: Protection and Control